Effects of a mindfulness-based intervention on symptoms and signs in chronic heart failure: A feasibility study. (1st January 2018) - Norman, Jonna; Fu, Michael; Ekman, Inger; Björck, Lena; Falk, Kristin
Abstract: Aims: Despite treatment recommended by guidelines, many patients with chronic heart failure remain symptomatic. Evidence is accumulating that mindfulness-based interventions (MBIs) have beneficial psychological and physiological effects. The aim of this study was to explore the feasibility of MBI on symptoms and signs in patients with chronic heart failure in outpatient clinical settings. Methods: A prospective feasibility study. Fifty stable but symptomatic patients with chronic heart failure, despite optimized guideline-recommended treatment, were enrolled at baseline. In total, 40 participants (median age 76 years; New York Heart Association (NYHA) classification II−III) adhered to the study. Most patients ( n =17) were randomized into MBI, a structured eight-week mindfulness-based educational and training programme, or controls with usual care ( n =16). Primary outcome was self-reported fatigue on the Fatigue severity scale. Secondary outcomes were self-reported sleep quality, unsteadiness/dizziness, NYHA functional classification, walking distance in the six-minute walk test, and heart and respiratory rates. The Mann–Whitney U test was used to analyse median sum changes from baseline to follow-up (week 10±1). Results: Compared with usual care (zero change), MBI significantly reduced the self-reported impact of fatigue (effect size −8.0; p =0.0165), symptoms of unsteadiness/dizziness ( p =0.0390) and breathlessness/tiredness related to physical functioning (NYHA class) ( p =0.0087). No adverse effects were found. Conclusions: In stable but symptomatic outpatients with chronic heart failure, MBI alleviated self-reported symptoms in addition to conventional treatment. The sample size is small and further studies are needed, but findings support the role of MBI as a feasible complementary option, both clinically and as home-based treatment, which might contribute to reduction of the symptom burden in patients diagnosed with chronic heart failure.